Influence of High Aspect Ratio Lead‐Free Piezoelectric Fillers in Designing Flexible Fibrous Nanogenerators: Demonstration of Significant High Output Voltage. Issue 10 (20th August 2019) - Bairagi, Satyaranjan; Ali, S. Wazed
Abstract : Engineering a flexible, cost‐effective piezoelectric energy harvester with a higher piezoelectric performance, i.e., higher voltage and power density, is a great technical challenge nowadays. Herein, the same target is set to demonstrate a unique nanogenerator comprising nanorods (aspect ratio of ≈8.5) of lead‐free potassium sodium niobate (KNN) and poly(vinylidene fluoride) (PVDF) where further poling process is fully omitted. The unique dimension of the synthesized rods with minimal loading (only 3%) bestows, somewhat surprisingly, a negative effect on beta nucleation but subdues this effect by the significant contribution toward the piezoelectric response by self‐orienting the dipoles at the electrospinning process by itself. Thus, the approach resolves the unmet task of complicacy in poling both the molecular and ionic dipoles at the same electric field in a subsequent poling of the finally formed nanocomposite. The nanodevice shows a higher open‐circuit output voltage of ≈17.5 V, an output current of ≈0.522 μA, and a current density of ≈0.13 μA cm −2 under repeated finger tapping and can power a light‐emitting diode (LED) of 2 V practically. The study opens a new route for excellent flexible piezoelectric nanogenerators for promising application in an enormous arena of self‐powering portable and wearable electronic gadgets. Abstract : A superior piezoelectric nanogenerator is developed using potassium sodium niobate (KNN) nanorods (NRs) incorporated into poly(vinylidene fluoride) (PVDF) electrospun nanocomposite with high aspect ratio (≈8.5). An addition of 3%‐KNN nanorods generates 17.5 V output voltage and 0.522 μA current. The higher aspect ratio of KNN NRs enhances piezoelectric performance through higher surface area and ionic dipoles in the nanogenerator.